Imaging ultra thin layers with helium ion microscopy: Utilizing the channeling contrast mechanism - Hlawacek, Gregor; Veligura, Vasilisa; Lorbek, Stefan; Mocking, Tijs F.; George, Antony; van Gastel, Raoul; Zandvliet, Harold J. W.; Poelsema, Bene (Beilstein Journal of Nanotechnology, 2012)
Background: Helium ion microscopy is a new high-performance alternative to classical scanning electron microscopy. It provides superior resolution and high surface sensitivity by using secondary electrons.Results: We report on a new contrast mechanism that extends the high surface sensitivity that is usually achieved in secondary electron images, to backscattered helium images. We demonstrate how thin organic and inorganic layers as well as self-assembled monolayers can be visualized on heavier element substrates by changes in the backscatter yield. Thin layers of light elements on heavy substrates should have a negligible direct influence on backscatter yields. However, using simple geometric calculations of the opaque crystal fraction, the contrast that is observed in the images can be interpreted in terms of changes in the channeling probability.Conclusion: The suppression of ion channeling into crystalline matter by adsorbed thin films provides a new contrast mechanism for HIM. This dechanneling contrast is particularly well suited for the visualization of ultrathin layers of light elements on heavier substrates. Our results also highlight the importance of proper vacuum conditions for channeling-based experimental methods.
Keywords: channeling; contrast mechanism; helium ion microscopy; ion scattering; thin layers

(untitled) - Ward, B. W.; Notte, J. A.; Economou, N. P. (J. Vac. Sci. Technol., B, 2006)

(untitled) - Hill, R.; Faridur Rahman, F. H. M. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2011)

(untitled) - Veligura, V.; Hlawacek, G.; van Gastel, R.; Poelsema, B.; Zandvliet, H. J. W. (Beilstein J. Nanotechnol., 2012)

(untitled) - Petrov, Y. V.; Vyvenko, O. F.; Bondarenko, A. S. (J. Surf. Invest.: X-Ray, Synchrotron Neutron Tech., 2010)

(untitled) - van Gastel, R.; Barriss, L.; Sanford, C.; Hlawacek, G.; Scipioni, L.; Merkle, A.; Voci, D.; Fenner, C.; Zandvliet, H.; Poelsema, B. (Microsc. Microanal., 2011)

(untitled) - Ramachandra, R.; Griffin, B.; Joy, D. (Ultramicroscopy, 2009)

(untitled) - George, A.; Knez, M.; Hlawacek, G.; Hagedoorn, D.; Verputten, H. H. J.; van Gastel, R.; ten Elshof, J. E. (Langmuir, 2012)

(untitled) - Hlawacek, G.; Puschnig, P.; Frank, P.; Winkler, A.; Ambrosch-Draxl, C.; Teichert, C. (Science, 2008)

(untitled) - Lorbek, S.; Hlawacek, G.; Teichert, C. (Eur. Phys. J.: Appl. Phys., 2011)

(untitled) - Mocking, T. F.; Hlawacek, G.; Zandvliet, H. J. W. (Surf. Sci., 2012)

SRIM, the stopping and range of ions in matter - Ziegler, J. F.; Biersack, J. P.; Ziegler, M. D. (Lulu Press, 2008)

(untitled) - Kinchin, G. H.; Pease, R. S. (Rep. Prog. Phys., 1955)

(untitled) - Singh, J.; Whitten, J. E. (J. Phys. Chem. C, 2008)

(untitled) - Wu, K.-Y.; Yu, S.-Y.; Tao, Y.-T. (Langmuir, 2009)